Insecticide contamination in organic agriculture: evidence from a long-term farming systems comparisons trial - Kampermann, I.; Bautze, D.; Mapili, M.; Musyoka, M.W.; Karanja, E.; Fiaboe, K.; Irungu, J.; Adamtey, N. (Elsevier, 2024)
Synthetic pesticides applied in conventional agriculture to control pests tend to compromise ecosystem services, and their residues may contaminate organic agriculture. To understand the significance of this contamination, also in small-scale farming systems in sub-Saharan Africa, quantitative data is required. Therefore, we compared synthetic insecticide and botanical/biopesticide residues in conventional and organic agricultural production systems after nine years of continuous cultivation of a maize-based crop rotation system at two sites in Kenya. Our results show high detectable concentrations of synthetic insecticide residues (imidacloprid, acetamiprid, chlorpyrifos, and chlorantraniliprole) in conventional plant produce and soil. Furthermore, the organophosphate chlorpyrifos was detected at concentrations above European Union Maximum Residue Limits (MRL) for plant produce, indicating potential risks for human health. Additionally, we detected imidacloprid, acetamiprid, chlorpyrifos, and chlorantraniliprole concentrations in the soil, indicating potential environmental harm. No residues of biopesticide/botanicals were detected in any of the production systems. However, we detected imidacloprid and chlorantraniliprole in organic plots. The findings indicate that the MRLs can be crossed even if synthetic insecticides are applied according to or below the recommended rates on the conventional plots. Thus, synthetic insecticides potentially risk human health and the environment, while botanicals and bio-pesticides represent a safe alternative.